Analisis Faktor-Faktor Yang Mempengaruhi Penerapan Etika Administrasi Publik di DPMPTSP Kota Padang - Sari, Novita Permata; Belpani, Nursuci Aryana; Safitri, Anggelina; Hanoselina, Yulia; Helmi, Rahmadhona Fitri (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
Public administration ethics plays an important role in ensuring the integrity and effectiveness of government services. This study aims to analyze the factors that influence the implementation of public administration ethics in the Capital Investment and One-Stop Integrated Service Office (DPMPTSP) of Padang City. Focusing on internal factors (intellectual, emotional, and spiritual intelligence) and external factors (organizational culture and laws and regulations), this study uses a qualitative approach through interviews, observations, and documentation analysis. This study is expected to provide valuable insights into the dynamics of ethics in public administration at the regional level, as well as provide recommendations to improve the quality of public services and employee integrity. The results of this study have the potential to contribute to the development of more effective public administration ethics policies and practices in Padang City and other regions.